Improving hindlimb locomotor function by Non-invasive AAV-mediated manipulations of propriospinal neurons in mice with complete spinal cord injury - Benedikt Brommer; Miao He; Zicong Zhang; Zhiyun Yang; Jessica C. Page; Junfeng Su; Yu Zhang; Junjie Zhu; Emilia Gouy; Jing Tang; Philip Williams; Wei Dai; et al. (Nature Communications, 2021)
After complete spinal cord injury, spinal segments below the lesion maintain inter-segmental communication via the intraspinal propriospinal network. Here, the authors show that neurons in these circuits can be chemogenetically modulated to improve locomotor function in mice after spinal cord injury.